Embracing E-Court Innovation: Advancing Maslahah Mursalah in Indonesia's Religious Courts - Yusnita, Eti; Yuswalina; Toriq, Muhammad (Universitas Islam Negeri Raden Fatah Palembang, 2024)
In this modern age, online litigation has become a game-changer in streamlining the judicial process. To embrace this transformation, Indonesia's Supreme Court has implemented an e-court system, governed by the Supreme Court Regulation, to boost efficiency and accessibility in the legal landscape. This study sets out to explore the advancements of the e-court system within Indonesia's Religious Courts, delving into the key factors driving its growth and shaping its implementation, with a focus on the concept of maslahah mursalah (public welfare). This study adopts a qualitative research approach, utilizing descriptive analysis and drawing upon both primary and secondary data sources. The findings highlight that while the e-court system largely aligns with existing regulations, hurdles like inadequate network infrastructure and limited public digital literacy persist. Nevertheless, the system brings substantial advantages, paving the way for meaningful progress, including lower costs, remote access to court services, and simplified processes. Key features such as e-filing, e-payment, e-summons, and e-litigation increase accessibility and convenience. Digital transformation reflects the issue of ensuring more efficient and cost-effective services. Factors that influence include cost savings from paperless processes, the ability to file cases remotely, technological literacy issues, and internet connectivity challenges in some areas. Overall, e-court systems align with societal welfare by enhancing the accessibility and affordability of legal services.